The amazing Maurice [videorecording (DVD)] - Rossio, Terry; Pratchett, Terry (Viva Pictures, 2024)
Maurice is a sassy, street-smart cat with a sneaky disposition. Together with his band of rats and pied-piper friend, Maurice travels across the countryside, swindling villagers with a staged rat plague. All seems to be going as planned until the gang arrives in a scenic market town and quickly realize something more nefarious is afoot.